Peran Penggunaan Bsi Mobile Banking Dalam Kemudahan Bertransaksi Di Era Modern - Audy Gesta Delila; Vivi Silvia (CV. ITTC INDONESIA, 2024)
Currently, sharia banking continues to develop various new innovations and new products that can provide the best service for bank customers and create something that follows developments in this modern era. One of the innovations brought about by sharia banks is the BSI Mobile application, which can be used for transactions and other things that are usually done by coming directly to the bank. BSI Bank is one of the banks that provides financial transaction services to customers called BSI Mobile. This research aims to determine the role of using BSI Mobile Banking in facilitating transactions in the current modern era for Indonesian people. Overall, the aim of establishing Mobile Banking is because it is practical, transactions are fast, and can make things easier for customers.